Electrophysiological Changes in Median Nerve among Young Male Cigarette Smokers (KYAMC Journal, 2024)
Background: Cigarette smoking has been associated with numerous cardiovascular and respiratory disorders. Chronic smoking may also disrupt neuronal function and damage neurons in the peripheral nervous system. Median nerve conduction study is an important electrodiagnostic test for the detection of peripheral nerve dysfunction. Objectives: To observe the impact of cigarette smoking on the electrophysiological status of median motor and sensory nerves in apparently healthy male cigarette smokers. Materials and Methods: This case-control study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka, from July 2017 to June 2018 on thirty male cigarette smokers aged 25 to 40 years. For comparison, thirty age and BMI matched non-smoker healthy male subjects were selected as controls. Motor and sensory nerve conduction parameters (latency, amplitude and nerve conduction velocity) of right median nerve were evaluated by standard methods, using standard nerve conduction study and electromyography machines in the Department of Neurology, Dhaka Medical College Hospital. For statistical analysis, unpaired t test was performed. Results: In this study, median sensory nerve latency was significantly prolonged (p ˂ 0.001) and sensory nerve conduction velocity was significantly slower (p ˂ 0.001) in cigarette smokers. The mean amplitude was also slightly reduced in smokers, but statistically, it was insignificant. However, the distal latency of median motor nerve was slightly prolonged whereas, the amplitude and motor nerve conduction velocity were slightly reduced in cigarette smokers in comparison to those of non-smokers. But the differences were not statistically significant. In addition, 10% of cigarette smokers had subclinical impairment in median sensory nerve function. Conclusion: Chronic cigarette smoking induces significant electrophysiological changes in median sensory nerve fibers and causes sensory nerve dysfunction, while it does not markedly affect median motor nerve fibers in young individuals.KYAMC Journal Volume: 15, No: 01, April 2024: 03-07.